Atmospheric fates of SO2 at the gas–solid interface of iron oxyhydroxide (FeOOH) minerals: effects of crystal structure, oxalate coating and light irradiance. Issue 1 (29th November 2022) - Wang, Wei; Li, Kejian; Liu, Yangyang; Gong, Kedong; Ge, Qiuyue; Wang, Longqian; Wang, Tao; Zhang, Liwu
Abstract : Heterogeneous SO2 conversion over FeOOH minerals leads to the considerable formation of atmospheric sulfate aerosols, influenced by crystal structure, light irradiance and oxalate coating. Abstract : Iron oxyhydroxide (FeOOH) is one of the most abundant atmospheric iron oxides. Considering their diverse emission features and reaction processes, airborne FeOOH minerals present distinct crystal structures and coating compositions. Nevertheless, little attention has been paid to the atmospheric fates of SO2 over the gas–solid interface of FeOOH, let alone the impacts of sunlight and its irradiance. Herein, by employing in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), the heterogeneous reaction of SO2 was investigated on nanoscale FeOOH with different crystal structures, followed by a discussion on the effects of oxalate coating and light irradiance. Results indicated that the heterogeneous uptake capacity varies with crystal structure (α-FeOOH > β-FeOOH > γ-FeOOH), probably due to the different structural properties of the exposed crystal structures. The presence of stimulated solar irradiation facilitates the conversion of SO2 on β-FeOOH and γ-FeOOH, whereas it inhibits the heterogeneous uptake on α-FeOOH. The addition of 5 wt% oxalate was discovered to significantly increase the reactive uptake coefficients of irradiated α-FeOOH and β-FeOOH by a factor of 3 and 2, which can be explained by the complex nature of iron with oxalate. The kinetic synergism between oxalate and sunlight was, for the first time, investigated in the heterogeneous regime of sulfate formation. The heterogeneous reactivity of FeOOH is nonlinearly correlated to light intensity and the exact dependence varies with crystal structure. This study contributes to a better understanding of atmospherically relevant heterogeneous reactions and haze formation, thus promoting laboratory studies and model simulations concerning atmospheric chemistry.